Motivation for Effectiveness of an Art Education Program - Satka, Fjoralba (Richtmann Publishing, 2012)
The article is based on my investigation in three directions revealing the main reasons for a contemporary arteducation program: the state of Albanian art education program in school, my research through an initial art project for childrenand teenagers with disabilities, and my program of art education for students in Pedagogy at the Faculty of Education,â€œAleksandÃ«r Moisiuâ€ University, DurrÃ«s, Albania.By focusing on the informative value of art and its role for psychological, mentaland cognitive development of personality, the analyses have the purpose to prove that Albanian art education is a case forchange. Albanian school has need of appropriately educated and trained teachers. The effective theoretical and practicalassistance of eligible art educators can play a key role in educating children and teenagers in competencies and skills in arts bywhich they can form their voice to express their particular experiences in variety of human conditions. This logically results in theuniversity education program in arts for students in pedagogy as future school teachers. The conclusions convincinglyemphasize the chances for success in quality of contemporary arts education. Improving its effectiveness through a more flexiblebetween the theory and practice pedagogy should be the base for an education project with long-term investment.